#$&* course Mth 279 6/20 1:30 Solve each equation:*********************************************
.............................................
Given Solution: ???Are you going to provide the given solutions to the homework’s once they are submitted??? &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): Had to look at chegg to review a similar problem from the book Was confused but slowly worked my way through problem ------------------------------------------------ Self-critique rating: ********************************************* Question: 2. y ' + t y = 3 t YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: p(t) = t int(p(t)) = t^2/2 y = Ce^(-t^2/2) + e^(-t^2/2) * int(e^(t^2/2)) *3t dt do u sub for integral let u= t^2 du= 2t y = Ce^(-t^2/2) + e^(-t^2/2) * 3/2int(e^.5u) du y = Ce^(-t^2/2) + e^(-t^2/2) * (3/2)*2e^(t^2/2) simplifying expression to: y = Ce^(-t^2/2) + 3 confidence rating #$&*: ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^ 1
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): slowly understanding process and general form ------------------------------------------------ Self-critique rating: ********************************************* Question: 3. y ' - 4 y = sin(2 t) YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: p(t) = -4 therefore int(p(t)) = -4t y = Ce^(4t) + e^(4t)*int(e^(-4t)*sin(2t)) use integration by parts twice u = sin(2t) du = 2cos(2t) dv=e^(-4t) v= (-1/4)e^(-4t) uv - int(v du) sin(2t)(-1/4)e^(-4t) - int((-1/4)e^(-4t)*2cos(2t) dt sin(2t)(-1/4)e^(-4t) + .5int(e^(-4t)*cos(2t))dt u=cos(2t) du=-2sin(2t) dv=e^(-4t) v=(-1/4)e^(-4t) sin(2t)(-1/4)e^(-4t) + .5((cos(2t))((-1/4)e^(-4t)) - int((-1/4)e^(-4t)*-2sin(2t)))dt therefore: int(e^(-4t)*sin(2t)) = -.25e^(-4t)sin(2t) + (1/8)e^(-4t)cos(2t) - .25int(e^(-4t)*sin(2t)) adding .25int(e^(-4t)*sin(2t)) to both sides you get: (5/4)int(e^(-4t)*sin(2t)) = -.25e^(-4t)sin(2t) + (1/8)e^(-4t)cos(2t) = 4/5(-.25e^(-4t)sin(2t) + (1/8)e^(-4t)cos(2t)) = (-1/5)e^(-4t)*sin(2t) - (1/10)e^(-4t)*cos(2t) Therefore: y = Ce^(4t) + e^(4t)*((-1/5)e^(-4t)*sin(2t) - (1/10)e^(-4t)*cos(2t)) distributing e^(4t) through y = Ce^(4t) - (1/5)sin(2t) - (1/10)cos(2t) confidence rating #$&*: ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^ 1
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): I found the integral long and difficult. I did int(e^(-4t)sin(2t) by parts twice; and it could just keep going around in circles because of the oscillating sin and e integrals. I had to look at wolfram alpha to help with the integral and to see to stop after the second by parts. Is there another way to go about solving this problem/integral??? ------------------------------------------------ Self-critique rating: ********************************************* Question: 4. y ' + y = e^t, y (0) = 2 YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: p(t) = 1 int(p(t)) = t y = Ce^-t + e^-t * int(e^t * e^t) dt y = Ce^-t + e^-t * int(e^(2t)) dt int(e^(2t)) dt = (1/2)e^(2t) y = Ce^-t + e^-t*(1/2)e^(2t) y = Ce^-t + (1/2)e^t 2 = Ce^(-0) + (1/2)e^0 2 = C + (1/2) C = 3/2 Therefore y = (3/2)e^-t + (1/2)e^t confidence rating #$&*: ^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^ 2
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): ------------------------------------------------ Self-critique rating: ********************************************* Question: 5. y ' + 3 y = 3 + 2 t + e^t, y(1) = e^2 YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY Your solution: p(t) = 3 int(p(t))= 3t y = Ce^(-3t) + e^(-3t)*int(e^(3t)*(3+2t+e^t))dt int(e^(3t)*(3+2t+e^t))dt distribute e^(3t) through and then make three separate integrals int(3e^(3t))dt + 2int(te^(3t))dt + int(e^(4t))dt middle integral done by parts where u = t du= dt dv=e^(3t) v=(1/3)e^(3t) 3((1/3)e^(3t) + (1/3)te^(3t) - (1/9)e^(3t) + (1/4)e^(4t) y = Ce^(-3t) + e^(-3t)(e^(3t) + (1/3)te^(3t) - (1/9)e^(3t) + (1/4)e^(4t)) y = Ce^(-3t) + (8/9) + (1/3)t + (1/4)e^t e^2 = Ce^(-3) + (8/9) + (1/3) + (1/4)e^1 Ce^(-3) = e^2 - (11/9) - (1/4)e C = e^5 - (11/9)e^3 - (1/4)e^4 y = (e^5 - (11/9)e^3 - (1/4)e^4)*e^(-3t) + (8/9) + (1/3)t + (1/4)e^t
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): I am not 100% confident on the math. I feel like I might have made a mathematical error
.............................................
Given Solution: &&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&& Self-critique (if necessary): ------------------------------------------------ Self-critique rating:" Self-critique (if necessary): ------------------------------------------------ Self-critique rating: ________________________________________ #$&*